Transmitter Gelombang Frekuensi Radio (RF) FM Berbasis Raspberry Pi - Ali Mustofa; Sigit Kusmaryanto; Rusli Ambarwati; Bravy Dwika Nanda (Jurnal FORTECH, 2022)
In recent years, technology in the telecommunications sector has developed rapidly, especially with the global situation encouraging the use of long-distance communications. One of these developments is the use of the Raspberry Pi, abbreviated as Raspi, as a substitute for conventional computers for receiving and transmitting FM radio signals. Raspberry Pi is a mini and portable computer that can be used as an alternative to conventional computers in general, such as the use of teleconference media, offices, Big Data, and as a video player with high resolution. The problem in using a computer as an FM radio signal transceiver system is its complex and expensive infrastructure. When compared to the Raspberry Pi 3 with a price range of IDR 500,000 - IDR 1,000,000, a transceiver system using conventional computers requires a computer in general at a price far exceeding the said price. Using Raspi makes it easy to transmit FM radio signals by simply coding through the Raspi terminal. In this study, the authors propose a transmitter system using a Raspberry Pi 3B+ which is connected to a dipole antenna at a working frequency of 100 – 101 MHz. Raspi is operated using the SSH protocol for remote desktops. The operating system used is Raspberry Pi OS with the use of a MAC computer (MAC OS) as a remote desktop. The results show that the Raspberry Pi device can be used to transmit FM radio signals at a frequency of 100 - 101 MHz. The dipole antenna tested using VNA (Vector Network Analyzer) with a length of 71 cm and a linear form can transmit a signal with a VSWR of 1.08 - 1.95:1 at a working frequency of 94.9 - 103.06 MHz and a return loss of -28.1 dBm at a frequency of 98.98 MHz.